The Effect of Self-Efficacy on the Adjustment of Out of Town College Students, with Peer Support as a Moderator Variable - Ratisya Rosiana; Munifah Munifah; Ikhlas Rasido; Hasan Hasan (Journal of Educational Sciences, 2026)
Students from out-of-town often face challenges in adjusting to their new environment in academic, social, and emotional aspects. This study aims to analyze the influence of self-efficacy and peer support on the adjustment of students from out-of-town, as well as to examine the role of peer support as a moderator variable. This study employs a quantitative approach with an ex post facto (causal-comparative) and cross-sectional design. The sample consists of out-of-state students in the Guidance and Counseling Program at Tadulako University, selected using purposive sampling. Data were collected via a Likert-scale questionnaire and analyzed using simple linear regression and Moderated Regression Analysis (MRA) with the aid of SPSS version 25. The results indicate that self-efficacy has a positive and significant effect on the adjustment of migrant students, contributing 49.4%. Additionally, peer support also has a significant effect on adjustment. Furthermore, the results of the moderation analysis indicate that peer support acts as a moderator variable that strengthens the influence of self-efficacy on adjustment, with an increase in the coefficient of determination to 57.3%. Thus, it can be concluded that self-efficacy and peer support are important factors in enhancing the adjustment abilities of migrant students.